Chromosome Translocation (Advances in Experimental Medicine and Biology,, 2018)
This volume discusses various aspects of mechanisms and methodologies of chromosome translocations, ranging from a historical and clinical overview of chromosome translocations to the rapid development of the next-generation sequencing technologies, which has dramatically increased our understanding of the spectrum of chromosome translocations in human diseases. The book also introduces the mechanistic studies on chromosome deletions and their implications in cancer, and discusses the mechanisms of regulating chromothripsis, a unique complex type of chromosome translocation. It is a valuable resource for students and researchers alike, providing insights into chromosome translocations and, potentially, other genomic aberrations involved in understanding and curing human diseases.